245 Comparing clinical and real-world outcomes for patients with endometrial cancer (EC) who have received prior platinum-based therapy. (18th September 2019) - Pothuri, B; Travers, K; Perhanidis, J; Gibson, CJ; Brown, J
Abstract : Objectives: Platinum and taxane-based therapy is considered standard for patients with newly diagnosed advanced/recurrent EC. We sought to compare post-platinum treatment outcomes between published and real-world sources. Methods: We searched PubMed (10 years) and Embase conference proceedings (3 years) for median OS (mOS), PFS (mPFS), ORR, and grade 3/4 adverse events (AEs) in advanced/recurrent EC, and compared to IBM® MarketScan® real-world US claims data (1/2014–11/2018). For MarketScan®, post-platinum therapy initiation (Index) represents the date of first EC drug claim after the end of platinum. Results: Data were extracted from 28 studies, including 4 controlled studies (3 randomized). Across studies, mOS was 9.6 mo (range 5.5–14.5 mo) and mPFS 2.8 mo (1.4–7.4 mo). Among the 5 studies with highest ORR, mPFS was 3.4 mo (3.0–7.4 mo). Most commonly reported grade 3/4 AEs were diarrhea (in 9/28 studies=32%), fatigue (8/28=29%), and anemia (7/28=25%). 1, 576 patients met the real-world inclusion criteria. Median follow-up was 9.3 mo post-Index, and median 29.6 mo pre-Index coverage. 76% of patients received initial platinum–taxane therapy, most commonly carboplatin–paclitaxel (63%). Post-Index, 48% of patients received monotherapy: 19% hormonal therapy, 9% liposomal doxorubicin, 5% bevacizumab, 3% taxane; ≤2% any other monotherapy. Besides carboplatin-paclitaxel (13%), ≤4% received any other combination regimen. Median duration of post-platinum treatment was 3.5 mo across regimens. Conclusions: Although chemotherapy and hormonal therapy are used for EC post-platinum, efficacy is lacking among reported studies and real-world data, and no uniform standard of care exists. More effective and tolerable therapies are needed for advanced/recurrent EC.